Vascular reconstruction after retroperitoneal and lower extremity sarcoma resection. Issue 2 (February 2017) - Wortmann, M.; Alldinger, I.; Böckler, D.; Ulrich, A.; Hyhlik-Dürr, A.
Abstract: Purpose: Soft tissue sarcomas (STS) of the retroperitoneum and the lower limb with invasion of major blood vessels are very rare malignancies. This study analyses the outcome of patients with vascular replacement during resection of STS of the retroperitoneum and the lower extremity with either arterial or concomitant arterial and venous infiltration. Methods: Patients with vascular replacement during resection of sarcoma of the retroperitoneum and the lower extremity between 1990 and 2014 were included in this retrospective single center study. Patients with a sole infiltration of a major vein were excluded. The follow up was obtained from medical records, the general practitioner and a clinical examination whenever possible. The main endpoints were survival, graft patency and the rate of major amputations. Results: Fourty seven patients were included in this study. Twenty patients have received an operation for a retroperitoneal STS, twenty seven for a STS of the lower extremity. The median follow-up was 24.5 months. The median survival was 113 months with a median tumor-free survival of 25 months. The two-year patency for arterial bypasses in the retroperitoneum and the lower extremity was 88% and 66%, respectively. Limb salvage rate was 89%. Conclusions: Invasion of major blood vessels is no contraindication for a resection of a STS in the retroperitoneum and the lower extremity, but it is accompanied by a high postoperative morbidity. Since surgical resection is the only curative therapy in these patients, it should also be offered to patients with infiltration of major blood vessels.